Acute renal allograft rejection after immune checkpoint inhibitor therapy for metastatic melanoma. (6th March 2016) - Spain, L.; Higgins, R.; Gopalakrishnan, K.; Turajlic, S.; Gore, M.; Larkin, J.
Abstract : This case of acute renal allograft rejection following treatment with immune checkpoint inhibitor therapy for metastatic melanoma emphasizes specific concerns regarding use of anti-PD-1 agents like nivolumab. Given rates of adverse events are generally much lower with anti-PD-1 antibodies compared with anti-CTLA-4 antibodies, there is potential for error in the generalization of perceived safety. Abstract: Immune checkpoint inhibitors such as ipilimumab and nivolumab improve survival in patients with advanced melanoma and are increasingly available to clinicians for use in the clinic. Their safety in organ transplant recipients is not well defined but published case reports describing treatment with ipilimumab have not been complicated by graft rejection. No cases of anti-programmed cell death protein 1 administration are reported in this group. We describe a case of acute graft rejection in a kidney transplant recipient after treatment with nivolumab, after progression on ipilimumab. Potential factors increasing the risk of graft rejection in this case are discussed, in particular the contribution of nivolumab.